Pendampingan Pelatihan Tari Sandur Manduro Pada Generasi Muda Desa Manduro Kabuh Jombang Untuk Membangun Kemandirian - Trinil Windrowati; Suwandi Widianto (Sekolah Tinggi Kesenian Wilwatikta (STKW) Surabaya, 2023)
Sandur Manduro is a performing art in the form of traditional theater which is rooted in or sourced from the people's way of life, born from the spontaneous life of the people of Manduro Village, Kabuh District, Jombang Regency. Sandur Manduro contains various elements of art, such as Fine Arts, Literary Arts, Music Arts and Dance Arts. Sandur Manduro's art has a ritual function, currently experiencing a decline in staging. There is no regeneration, because the Sandur Manduro players are old enough to be one of the problems. Through the Community Partnership Program (PKM) it is hoped that Sandur Manduro will be independent. One of the methods used is to provide training assistance for the Sandur Manduro dance for the younger generation of Manduro Village.